224k views
2 votes
6x^{2} + 19 + 9x^{2} - 8
With Explanation

User Aalbahem
by
5.1k points

1 Answer

5 votes

Answer:

I'mnot sure if you're asking for its roots..but here you go :)

Explanation:


= 6 {x}^(2) + 19 + 9 {x}^(2) - 8 \\ = (6 {x}^(2) + 9 {x}^(2) ) + (19 - 8) \\ = 15 {x}^(2) + 8 \\ 15 {x}^(2) = - 8 \\ {x}^(2) = - (8)/(15) \\ \sqrt{ {x}^(2) } = \sqrt{ - (8)/(15) } \\ x = \sqrt{ (8)/(15)} * √( - 1) \\ x = \sqrt{ (8)/(15) } * i \\ x1 = 0.7302i \\ x2 = - 0.7302i

User Karishma Gulati
by
5.6k points